Культура мовлення у професійній діяльності - Новіченко, Є. О. (ХНУРЕ, 2023)
Language is one of the indicators of human intellectual development. The way she speaks or writes indicates her spiritual development. Mastery of a cultural language is an important skill for the entire society, as well as a kind of indicator of professional suitability for people of various professions: diplomats, lawyers, politicians, teachers of schools and universities, radio and television workers, journalists, managers, etc. The culture of speech is important for everyone who, by nature of their activity, is connected with people, organizes and directs their work, teaches, educates, conducts business negotiations, and provides various services to people.